Réponses

2013-11-27T15:15:09+01:00
Bonjour !
1/ a) A = -1/2 + 5/2 x (1 - 1/2) = -1/2 + 5/2 x 1/2
                                            = -1/2 + 5/4
                                            = 3/4
       B = 5/7 : 6/7 - (1/2 - 1) = 5/6 - (-1/2)
                                         = 5/6 + 1/2
                                         = 8/6
                                         = 4/3
     b) A = 3/4 = 1/(4/3) = 1/B
        Donc A est l'inverse de B, et aussi B est l'inverse de A
2/ a) PGCD(2482,1825) = 73
    b) 2482/1825 = (2482/73)*(73/1825) = 34/25

Bon courage ^_^